1996
DOI: 10.2190/bcwl-bl0j-nly2-k161
|View full text |Cite
|
Sign up to set email alerts
|

Survivors of Suicide: A Comprehensive Bibliography Update, 1986–1995

Abstract: An update of a 1985–86 Omega bibliography of the literature on survivors of suicide is presented. Following brief introductory comments, including the identification of research and therapy needs and unresolved issues, the bibliography listings are organized by the following subtopics: general references on family members and friends as suicide survivors; children, adolescents, youth, and parents as survivors; school and educational settings; parental suicide; elderly suicide survivors; mental health professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 139 publications
0
4
1
3
Order By: Relevance
“…The movement was promoted by the book Survivors of Suicide by Albert C. Cain (1972), who was probably responsible for its name. These topics continue to have broad coverage in U.S. and European suicide literature; however, McIntosh (1996) Albert C. Cain (1972) noted that after having reviewed studies from 1985–1996, little was known about the impact of a patient's suicide on professional caregivers. Shortly thereafter, Hendin et al (2000) reported the results of their study of therapists for 26 patients who committed suicide and had completed a semistructured questionnaire about their reactions.…”
mentioning
confidence: 99%
“…The movement was promoted by the book Survivors of Suicide by Albert C. Cain (1972), who was probably responsible for its name. These topics continue to have broad coverage in U.S. and European suicide literature; however, McIntosh (1996) Albert C. Cain (1972) noted that after having reviewed studies from 1985–1996, little was known about the impact of a patient's suicide on professional caregivers. Shortly thereafter, Hendin et al (2000) reported the results of their study of therapists for 26 patients who committed suicide and had completed a semistructured questionnaire about their reactions.…”
mentioning
confidence: 99%
“…Auch der Suizid eines Kollegen kann professionelle Helfer zu Suizidhinterbliebenen machen ( [41], vgl. [2]). Einige Publikationen auf diesem Gebiet veranschaulichen einerseits die Belastung, die durch einen Suizid im professionellen Umfeld entstehen kann, und verdeutlichen andererseits die Notwendigkeit von Maûnahmen, die den negativen Effekten dieses Stressors und einem möglicherweise damit in Verbindung stehenden Burnout-Syndrom entgegenwirken können (vgl.…”
Section: Professionelle Helfer Als Suizidhinterbliebeneunclassified
“…Einige Publikationen auf diesem Gebiet veranschaulichen einerseits die Belastung, die durch einen Suizid im professionellen Umfeld entstehen kann, und verdeutlichen andererseits die Notwendigkeit von Maûnahmen, die den negativen Effekten dieses Stressors und einem möglicherweise damit in Verbindung stehenden Burnout-Syndrom entgegenwirken können (vgl. [2]). In wie vielen Fällen auf einen Suizid im professionellen Umfeld tatsächlich mit postventiven Maûnahmen reagiert wird [42], ist jedoch nicht klar.…”
Section: Professionelle Helfer Als Suizidhinterbliebeneunclassified
“…Dabei hatte Litman bereits 1965 [16] unter dem Titel ¹When patients commit suicideª in der renommierten amerikanischen Fachzeitschrift für Psychotherapie auf die Problematik für den Therapeuten hingewiesen. Die Zahl der Publikationen, die dieses Thema diskutieren, hält sich jedoch in sehr engen Grenzen [17,30] handlung. Körperliche Erkrankung, Depressivität, irrationale Angstzustände und Verschlechterungen von persönlichen und professionellen Beziehungen wurden beobachtet; auch Phänomene von Depersonalisation und vermehrte Distanzierung von Patienten aber auch von Kollegen ebenso wie nachfolgendes Überengagement in der professionellen Rolle, Angst vor dem ¾rger der Familie des Suizidenten oder vor rechtlichen Konsequenzen oder auch vor Beeinträchtigungen der eigenen Karriere.…”
Section: Introductionunclassified